Heck arylation of the natural pyrethrins. (9th January 2023) - Markham, Todd E.; Duggan, Peter J.; Johnston, Martin R.
Abstract: The natural pyrethrins have served as reliable active ingredients in insecticidal formulations and remain ideal due to their environmentally friendly characteristics. This work focussed on the elaboration of the pyrethrin scaffold utilising the palladium catalysed Heck reaction. Utilisation of cationic reaction conditions led to the production of 24 arylated pyrethrin derivatives with a range of substituted aromatic moieties containing ( E, E ) geometry of the rethrolone side chain. Graphical abstract: Image 1